Vitamin D and C Supplementation as an Adjunct to Non-surgical Therapy in the Treatment of Chronic Periodontitis: A Clinical Study - Mohammed, Rafah Hussein; Mousa, Hashim Dawood; Mohammed, Saeed Ali; Karam, Bangeen Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2024)
Background: Periodontitis is a common disorder affecting the bone and soft tissues of the periodontal complex. When untreated, it may lead to severe mobility or even loss of teeth. Recent studies highlight the alleged role of vitamin C (Vit C) and vitamin D (Vit D) in developing the disease. Objectives: To summarize recent knowledge on the role of Vit C and Vit D in the pathogenesis and treatment of periodontitis. Patients and methods: Forty-five patients with moderate to severe chronic periodontitis were selected and randomly divided into three equal groups. The first group was the control group, which underwent scaling, polishing and root planning (SRP; conventional periodontal treatment) without medication. The second group underwent SRP and received Vit D3 (1000 IU) with Vit C (500 mg) orally and daily. The third group received Vit D3 (1000 IU) with Vit C (500 mg) orally and daily without SRP. All treatments were continued for two months. Then, plaque index (PI), gingival index (GI), and clinical attachment loss (CAL) were evaluated after two months. Results: Significant PI, GI, and CAL reductions were detected after two months of periodontal treatment with Vit D3 and C supplementation in the second group compared to other groups. Conclusions: Vit C and Vit D reduced gum bleeding and can be used to improve patient's quality of life.
Keywords: Periodontitis vitamin supplementation quality of life; plaque index; gingival index; and clinical attachment loss